Behind copper prices: a historical perspective 1850-1950 - Marc Badia-Miró; Anna Carreras-Marín; Cristián Ducoing (Lund University, School of Economics and Management, LUSEM Sustainability Research Network, 2019)
Commodity prices and their secular trends are at the core of many different development theories, particularly relevant for the Latin American region, like the Prebisch-Singer hypothesis, the natural resource curse theory or the somehow malthusian scarcity prediction. In this article we review the international copper price indices available in the literature and we compare them with a new data set, elaborated from the Official Foreign Trade statistics of one of the main copper producers (Chile) This data has included information on value added and several price/volume indicators allowing to elaborate a more accurate copper price estimation in the long run. This information will enhance our knowledge on commodity prices, mineral trends and structural change.
Keywords: N16; N50; Q32; 330; Copper prices; product diversification; Natural Resources; Price Indices